Working and Learning during the COVID-19 Confinement: An Exploratory Analysis with a Small Sample from Portugal - Martins, Alexandra Dias (2021)
The epidemiological situation caused by the COVID-19 pandemic led to efforts to mitigate the transmission of the infection, forcing workers and students to stay at home. Universities closed, as did many businesses, forcing education and work to adapt to the new situation. While for some people it was a positive experience, for others it was not. This article analyzes the responses of 89 respondents, over 18 years old, in teleworking or enrolled in university online education, in a survey at the beginning of 2021, when Portugal was in a new state of emergency. Variables such as gender, age and parenthood were used, as well as ownership of equipment, own workspace, and quality of internet, comparing distance learning/work with traditional methods and measuring levels of satisfaction and willingness to adopt this model in the future. These results suggest an association of gender and parenting in the valuation of telework/distance education; women were more positive than men and participants with children were more positive than participants without children. The same was the case for respondents with their own workspace and better-quality internet. There is a strong relation between paternity and the preference for the distance model, in the sense of valuing the distance model, as well as a relation between those who have their own work space and the appreciation of the distance model. In general, respondents to our survey showed that they are not fond of adopting telework/distance learning in the future.